Consider the Risk of Vesicouterine Fistula in the Event of Intermittent Fluid Vaginal Discharge after a Cesarean Section - Talla, Pascal; Ekotomati, Maria; Brünisholz, Yves; Bouquet de la Jolinière, Jean; Fagan, Bernice; Feki, Anis; Ben Ali, Nordine (Frontiers in Surgery, 2017)
Though the number of Vesicouterine Fistulas is steadily increasing in association with the increasing number of Caesarean Sections, clinical presentation can be subtle and not easily identified. In this Case Study we will review the presenting symptoms of this complication and suggest an updated management protocol.